HETEROSIS IN SINGLE CROSS INTER AND INTRA-SPECIFIC HYBRIDS OF DESI COTTON IN RELATION TO SEED COTTON YIELD AND IT’S CONTRIBUTING CHARACTERS - RAKESH CHOUDHARY,; B. G. SOLANKI,; RAMESH CHOUDHARY,; AKHILESH KUMAR SINGH,; VIKASKHANDELWAL, (The Bioscan, 2014)
Forty five inter and intra-specific hybrids between G. arboreum and G. herbaceum derived from ten genotypes (five G. arboreum and five G. herbaceum) in half diallel mating design were evaluated to study heterosis for seed cotton yield and its component traits. For seed cotton yield, 17 crosses showed significant positive heterosis over better parent and five crosss showed significant positive standard heterosis over commercial check, G. Cot DH7. In order of merit F1 hybrids GBhv- 282 x G 27 (67.36%), GBhv- 287 x 824 (58.14%), GBhv- 282 x GAM- 173 (35.00%), GBhv- 286 x G 27 (20.50%), and GBhv- 283 x 824 (18.75%) recorded highest significant positive standard heterosis while the maximum heterobeltiosis for seed cotton yield per plant was exhibited by the hybrid GBhv- 287 x 824 (155.60 %) followed by GBhv- 282 x G 27 (151.29%) and GBhv- 282 x GAM- 173 (130.30%). Similar trend of heterosis for numbers of boll per plant were observed in above hybrids. The present study reveals good scope for isolation of pure lines from the progenies of heterotic F1s as well as commercial exploitation of heterosis in desi (diploid) cotton.